Determinan Terhadap Transfer Pricing Melalui Tax Minimization Sebagai Pemoderasi - Ema Mardiana; Achmad Badjuri (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the effect of tunneling incentives, bonus mechanism, and company size on transfer pricing with tax minimization which acts as a moderating variable. Case studies with qualitative research method are used as a strategy in this research. The research population uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Purpose sampling was used for the sampling procedure with a total of 81 companies according to the criteria after being multipled by 3 years of observation. The analytical method used is Moderating Regression Analysis (MRA). The results of the study show that tunneling incentives have an effect on transfer pricing, while the bonus mechanism and firm size have no effect on transfer pricing. Tax minimization is able to moderate the effect of the bonus mechanism on transfer pricing, but tax minimization is not able to moderate the relationship between tunneling incentive, company size and transfer pricing.